Design of BIPA learning based on short story “Basa-Basi” for understanding the phenomenon of chit-chat in Indonesian society - Rudi Ekasiswanto; Kurniawati , Wira; Warouw , Nicolas (Universitas Ahmad Dahlan, 2024)
Chit-chat is a socio-cultural phenomenon ethnographically embedded in Indonesian society's culture, also discursively presented in literary works, namely the short story